Improvements in health status and utility associated with ataluren for the treatment of nonsense mutation Duchenne muscular dystrophy. Issue 3 (13th January 2020) - Landfeldt, Erik; Lindberg, Christopher; Sejersen, Thomas
Abstract: Introduction: Little is known of the impact of ataluren on health status and utility in patients with nonsense mutation Duchenne muscular dystrophy (nmDMD). In this work we sought to investigate the clinical expert consensus of these topics in a Delphi panel study. Methods: Six Swedish neuromuscular experts participated in this study. Consensus was investigated for responses to the Health Utilities Index (HUI) and a visual analog scale (VAS) for ambulatory and nonambulatory patients treated with ataluren plus best supportive care vs best supportive care alone. Results: Consensus was obtained after three panel rounds across treatments and disease stages, except for HUI question 10 (ability to use hands and fingers) for nonambulatory patients. Utility differences between treatments were 0.31 for ambulatory patients, and 0.15 to 0.18 for nonambulatory patients, respectively. The corresponding VAS differences were 12 and 13. Discussion: The outcomes of this study support the association of ataluren for the treatment of nmDMD with improved health status and utility.